TNFRSF11B Suppresses Memory CD4+ T Cell Infiltration in the Colon Cancer Microenvironment: A Multiomics Integrative Analysis - Zhang, Jun-rong; Hou, Ping; Wang, Xiao-jie; Weng, Zong-qi; Shang-guan, Xin-chang; Wang, Hui; You, Fang; Lin, Bing-qiang; Huang, Zheng-yuan; Chen, Xian-qiang (Frontiers in Immunology, 2021)
Background: Colorectal cancer is lethal cancer in the world, due to the low tumor mutation burden and low proportion of tumor-infiltrating lymphocytes in the microenvironment of most patients, innovative immunotherapeutic approaches need to be identified. Methods: Using the TCGA-COAD dataset (n = 514), we identified TNFRSF11B as a prognostic factor of colon cancer. Immunohistochemistry (IHC) dataset (n = 86), 290 single colorectal cancer cells (GSE81861), and 31 paired colon cancer transcriptional datasets were further applied to validate the function of TNFRSF11B, which was confirmed via fluorescence-activated cell sorting (FACS) analysis. Results: A risk scores system consisting of eight IRGs (FGFR2, ZC3HAV1L, TNFRSF11B, CD79A, IGHV3-11, IGHV3-21, IGKV2D-30 and IGKV6D-21) was constructed to predict the prognosis of colon cancer patients. Only TNFRSF11B closely correlated with late-stage, lymph node metastasis and worse survival outcomes (p=0.010, p=0.014 and p=0.0061). In our IHC dataset, 72.09% (62/86) of the colon cancer patients had an overexpression of TNFRSF11B with significantly shorter overall survival times (p=0.072). High TNFRSF11B expression typically had a later TNM-stage (p=0.067), higher frequency of lymph node (p=0.029) and lymphovascular invasion (p=0.007), and higher incidence of pneumonia (p=0.056) than the counterpart. Six genes (KRT18, ARPC5L, ACTG1, ARPC2, EZR, YWHAZ) related to pathogenic E. coli. infection, were simultaneously increased with TNFRSF11B overexpression via GESA analysis. These genes involved in the regulation of actin cytoskeleton, shigellosis, bacterial invasion of epithelial cells and Salmonella infection. Finally, only activated memory CD4+ T cells (p=0.017) were significantly decreased in high TNFRSF11B expression group via CIBERSORT comparison, which was confirmed by TIMER2.0 analysis of TCGA-COAD dataset. We also performed FACS to illuminate that TNFRSF11B downregulate the immune activity of central memory CD4+ T cells and effector memory CD4+ T cells (all p<0.001). Conclusion: TNFRSF11B, acts as a prognostic factor for colon cancer patient, could affect colon cancer immune response. TNFRSF11B was closely related with lymph node invasion and pathogenic E. coli. infection, which might negatively affect memory activated CD4+ T cell infiltration in colon cancer.